Evaluation of Insecticides and Fungicides for the Management of Insect Pests and Diseases of Tomato (Solanum lycopersicum L.) - Garmonyou, Aloysius Sam (2013)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, in partial fulfillment of the requirements for the Degree Of Master of Science In Crop Protection (Entomology),